Antiglycation and antitumoral activity of Tribulus terrestris dry extract - Malaguti Figueiredo, Celia Cristina [UNESP]; Gomes, Amanda Costa [UNESP]; Granero, Filipe Oliveira [UNESP]; Bronzel Junior, Joao Luiz [UNESP]; Silva, Luciana Pereira; Tasca Gois Ruiz, Ana Lucia; Goncalves da Silva, Regildo Marcio [UNESP] (Mashhad Univ Med Sciences, 2021)
Objective: Investigation of the antiglycation and antitumoral potential of standardized and saponins-enriched extracts of Tribulus terrestris herbal medicine. Materials and Methods: The procedures for the evaluation of the antiglycation activity of the standardized (TtSE) and saponins-enriched (TtEE) extracts of T. terrestris were: determination of relative mobility in electrophoresis (RME), free amino groups using OPA method and advanced glycation end-products (AGEs) fluorescence. Antioxidant activity was determined by DPPH radical scavenging test. In vitro antitumor activity of TtSE and TtEE was evaluated in human tumor cell lines. Results: The results were obtained by antiglycation tests (RME, OPA method and AGEs fluorescence determination), using BSA as protein and ribose as glycation agent, and antioxidant assay (DPPH test); it was verified that both extracts of T. terrestris have antiglycation and antioxidant activity. In addition, the extracts were able to induce death of more than 50% of human tumor cell lines. Conclusion: The present study showed that standardized and saponins-enriched extracts of T. terrestris herbal medicine present antiglycation and antioxidant and antiproliferative action in human tumor cells lines. The saponins-enriched extract proved a greater antiglycation and antioxidant activity in comparison to the standardized type.
Keywords: Tribulus terrestris; Antiproliferative; Protein glycation; Steroidal saponins